2007
DOI: 10.1016/j.jcrs.2006.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating keratoplasty versus intrastromal corneal ring segments to correct bilateral corneal ectasia: Preliminary study

Abstract: Eyes with Intacs had a shorter recovery time than eyes having PKP. The eyes with Intacs had no complications. Complications in eyes with PKP included cataract, graft rejection, and elevated intraocular pressure. Thus, Intacs segments may delay or prevent the need for a corneal graft, although longer follow-up is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…To our knowledge, there is only 1 similar study in the peer-reviewed literature. The study by Rodríguez et al 38 compared PKP and ICRS outcomes in cases of bilateral corneal ectasia. In their study, the authors found that Intacs segment (Addition Technology, Inc.) implantation in eyes with keratoconus avoided scarring due to contact lenses, improved visual function, and reduced the need for PKP with its inherent risks of rejection and other significant complications.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is only 1 similar study in the peer-reviewed literature. The study by Rodríguez et al 38 compared PKP and ICRS outcomes in cases of bilateral corneal ectasia. In their study, the authors found that Intacs segment (Addition Technology, Inc.) implantation in eyes with keratoconus avoided scarring due to contact lenses, improved visual function, and reduced the need for PKP with its inherent risks of rejection and other significant complications.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a study of microkeratome-assisted lamellar keratoplasty for keratoconus, 16% of eyes had a UDVA of 0.10 or better and 88% had a CDVA of 0.50 or better 1 year after surgery. 17 The complication rates are of particular importance in more invasive keratoplasty techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Intrastromal corneal ring segments, including Intacs (Addition Technology Inc.) and KeraRings intracorneal ring segments (Ferrara Ophthalmics), may improve visual function with corneal ectatic diseases (3*,5*,8–10*). They improve visual function by potentially decreasing irregular astigmastism and reducing corneal steepening (9).…”
Section: Intracorneal Ring Segmentsmentioning
confidence: 99%
“…They improve visual function by potentially decreasing irregular astigmastism and reducing corneal steepening (9). The rings are inserted in a concentric deep intrastromal tunnel created with either a microblade or a femtosecond laser (8,11). The ring segments are peripherally space-occupying, which induces central corneal flattening (10*).…”
Section: Intracorneal Ring Segmentsmentioning
confidence: 99%